1994
DOI: 10.1111/j.1349-7006.1994.tb02382.x
|View full text |Cite
|
Sign up to set email alerts
|

Salty Food Intake and Risk of Helicobacter pylori Infection

Abstract: To clarify the risk factors for Helicobacter pylori infection, which is considered to play an etiologic role in atrophic gastritis, duodenal ulcer and gastric cancer, various parameters including diet and socioeconomic characteristics were compared between H. pylori‐infected and non‐infected men. In a cross‐sectional study of 634 men aged 40 to 49 years selected randomly from five areas with different rates of gastric cancer mortality, 474 of 628 men evaluated were positive for IgG antibody against H. pylori. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
1

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(86 citation statements)
references
References 14 publications
1
84
0
1
Order By: Relevance
“…A previous epidemiologic study suggested that the consumption of salty foods increased the risk of H. pylori infection. 16 In our study, we observed that salt intake exhibited a stronger association with ⑀dA excretion than with -6 PUFA intake. Increased oxidative stress and involvement of excess NO production has been reported in H. pylori infected persons.…”
Section: Etheno Adducts In Urinesupporting
confidence: 44%
“…A previous epidemiologic study suggested that the consumption of salty foods increased the risk of H. pylori infection. 16 In our study, we observed that salt intake exhibited a stronger association with ⑀dA excretion than with -6 PUFA intake. Increased oxidative stress and involvement of excess NO production has been reported in H. pylori infected persons.…”
Section: Etheno Adducts In Urinesupporting
confidence: 44%
“…Helicobacter pylori infection is closely associated with the risk of gastric cancer (Huang et al, 1998;Helicobacter and Cancer Collaborative Group 2001). The prevalence of H. pylori IgG antibody among randomly selected men aged 40 -49 years was 76% in Ninohe, 86% in Yokote, 72% in Saku and 63% in Ishikawa PHC areas in our previous ecological study in 1989-1990(Tsugane et al, 1994, which nearly paralleled age-adjusted incidence rates of gastric cancer in each area (Table 1). However, consumption of salted fish roe and salted fish preserves in these male cohort subjects was also closely associated with gastric cancer incidence at the population level: 5.8 and 4.3 days month À1 in Ninohe, 7.9 and 4.9 days month À1 in Yokote, 4.3 and 3.8 days month À1 in Saku and 0.9 and 1.0 days month À1 in Ishikawa .…”
Section: Discussionmentioning
confidence: 66%
“…The induced proliferous change may enhance the effect of food-derived carcinogens (Takahashi and Hasegawa, 1985). Such mucosal damage also enhances H. pylori colonisation in mice (Fox et al, 1999) and possibly in humans (Tsugane et al, 1994), thereby inducing chronic gastritis (Blaser, 1990) and possibly increasing the risk of gastric cancer (International Agency for Research on Cancer, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous prospective cohort study showed that HP infection significantly increased the risk of stomach cancer in males (RR=2.59, 95% CI=1.03 -6.50) but not in females (RR=0.99, 95% CI=0.36 -2.68) (Yamagata et al, 2000). A high consumption of pickled vegetables and miso soup significantly increased HP infection (OR=1.9, 95% CI=1.10 -3.30 and OR=1.60, 95% CI=1.03 -2.49, respectively) (Tsugane et al, 1994). High-salt diets contribute to expansion of HP colonisation (Fox et al, 1999), therefore, our present results may be affected by HP infection.…”
Section: Discussionmentioning
confidence: 95%